Estudo de políticas públicas voltadas para primeira infância: o Programa Criança Feliz no Rio Grande do Sul, a partir das perspectivas de seus agentes - Mesquita, Lediane Ferreira (2022)
Healthy early childhood is essential for children's development, and the family is fundamental for this result, as the stimuli they receive in the environment in which they are inserted will expand or restrict their potential in child growth. Thus, in addition to day care centers for children, linked to public educational policy, thinking about complementary public policies aimed at early childhood is essential in a continental country such as Brazil. With the Coronavirus (COVID-19) pandemic, a situation emerged, until then, little imagined in the school and family universe and only reinforces the need for public policies aimed at early childhood. In order to reach this target audience, the Happy Child Program (PCF) was created by the Federal Government, with the purpose of providing the integral development of children in early childhood, taking into account their families and their living conditions. The present work deals with public policies for early childhood, highlighting the PCF and identifying, through interviews, the agents' perspective on the program. For a better understanding and improvement of the subject, concepts and studies by authors on legislation, development and characteristics are discussed. Therefore, as a source of primary data, a qualitative study was carried out through semi-structured interviews with agents (supervisors and social workers) from the municipalities of Dom Pedrito and Tenente Portela of Rio Grande do Sul, online and by telephone due to the COVID-19 pandemic. The interview protocol is divided into seven blocks: Profile of the agents of the Criança Feliz Program; Operational knowledge of the agents of the Happy Child Program; Quality of the structural elements of the Happy Child Program; Understanding the variables of the Happy Child Program; Interaction between the actors of the Criança Feliz Program, Services provided to beneficiaries and on the Criança Feliz Program. And to evaluate the Criança Feliz Program according to the perception of its visitors, as secondary data sources, data from the project carried out in 2020 was used: Qualitative evaluation of the perception of results of the Happy Child Program with its beneficiaries and agents: analysis of Public Policy for Early Childhood Care, Federal University of Santa Maria (UFSM). Data analysis was performed manually with the aid of Brynard's 5C Protocol, bibliographic research, transcripts of interviews, content analysis, where opinions, difficulties and evaluations exposed by the agents of the Happy Child Program are exposed. The main results show that the materials needed for the Happy Child Program are offered, but it needs a new computer and an individualized room for consultations. As for the Administration of the Program, it should be noted that the number of services provided by the Program is sufficient; the policy for families' access to the Program is good, but it would need to offer more vacancies and collaborators. The interaction of agents with the beneficiary family, service colleagues and the social assistance network is very good, and the visitors are more intimate with the families. All agents highlighted the importance of the contributions of their work to the Program, the recognition and acceptance of society, they also considered the duration of the visits to be adequate. Finally, it was noticed that the commitment of the agents is satisfactory, most of them manage to fulfill their tasks and all find the service time adequate, the articulation between those involved in the Program is pleasant and productive, the communication is very good and intense.